Soil remediation for contaminated soil from heavy metals by electrokinetic process / Sabariah Arbai ... [et al.] - Arbai, Sabariah; Awang, Haryati; Salleh, Sabiha Hanim; Abu Bakar, Azinoor Azida; Mohamed, Zainab (Research Management Institute (RMI), 2012)
Contaminated sites with heavy metals, organic compounds and hazardous materials added with inefficient waste handling techniques, leakages and untreated abandoned mines made enormous impact to groundwater quality, soils and ecosystems. Electro-chemical principle, known as electrokinetic method is a greatly potential treatment of heavy metal in contaminated soils, including soils of low permeable clays (Rutigliano et.al 2008); and groundwater (Cherifi et.al., 2009). (Colletta et.al., 1997) stated that purging liquids of certain pH is important for heavy metal migration and molar concentration, while Fabienne et.al. (1999) stated that temperature mainly influences the ionic velocities with changes in partitioning of heavy metals. The study will identify and evaluate the amount of heavy metals in the collected contaminated soil samples, investigate physical characteristics of soils and relate to the chemical concentration levels of heavy metals, thus recommending the optimum temperature for efficient removal of heavy metals with appropriate pH. In this study, there are two types of specimen, i) site specimen, and ii) prepared specimen. For the site specimen, the physical characteristics and chemical concentration will be identified. For chemical concentration of both site and prepared samples, samples are digested and analyzed using ICP-MS equipment. For the prepared specimen, fresh clay specimen are spiked, compacted of low concentration heavy metals and will be run using electrokinetic under controlled pH and temperature. The purging liquids will be prepared in the electrode reservoirs to provide an appropriately-controlled pH for heavy metals adsorption. The electrokinetic tests will be performed onto 80 prepared spiked samples with initial concentration to a final concentration, each set of 240 hrs duration, temperature set and observed with daily pH monitored and recorded. The removal efficiency for optimal heavy-metal desorption, initial and final pH of the slurry specimen at 5 positions on the test-cell will be recorded, computed and analyzed.